It’s a helluva journey: a qualitative study of patient and clinician experiences of nausea and vomiting syndromes - Sebaratnam, Gabrielle; Law, Mikaela; Broadbent, Elizabeth; Gharibans, Armen A.; Andrews, Christopher N.; Daker, Charlotte; O’Grady, Greg; Calder, Stefan; Keane, Celia (Frontiers in Psychology, 2023)
Background: Chronic gastroduodenal disorders including, chronic nausea and vomiting syndrome, gastroparesis, and functional dyspepsia, are challenging to diagnose and manage. The diagnostic and treatment pathways for these disorders are complex, costly and overlap substantially; however, experiences of this pathway have not been thoroughly investigated. This study therefore aimed to explore clinician and patient perspectives on the current clinical pathway.Methods: Semi-structured interviews were conducted between June 2020 and June 2022 with 11 patients with chronic nausea and vomiting syndrome alone (based on Rome IV criteria) and nine gastroenterologists who treat these conditions. Interviews were recorded, transcribed, and thematically analysed using a reflexive, iterative, inductive approach. Five key patient themes were identified: (1) the impacts of their chronic gastroduodenal symptoms, (2) the complexity of the clinical journey, (3) their interactions with healthcare providers, (4) the need for advocacy, and ( 5) their experience of treatments. Five key clinician themes were also identified: (1) these conditions were seen as clinically complex,(2) there is an uncertain and variable clinical pathway, (3) the nuance of investigations, (4) these conditions were difficult to therapeutically manage, and (5) there are barriers to developing a therapeutic relationship.: Findings indicate that both patients and clinicians are dissatisfied with the current clinical care pathways for nausea and vomiting syndromes. Recommendations included the development of more clinically relevant and discriminant tests, standardisation of the diagnostic journey, and the adoption of a multidisciplinary approach to diagnosis and treatment.